2012
DOI: 10.1007/s00520-012-1390-2
|View full text |Cite
|
Sign up to set email alerts
|

Depression, fatigue, and health-related quality of life in head and neck cancer patients: a prospective pilot study

Abstract: Depression and fatigue symptoms increased during radiotherapy treatment, while QoL levels decreased. This demonstrates that these symptoms are strongly correlated and that their presence negatively influenced QoL. At the start of treatment, nurses need to advise patients and plan care, offering interventions to decrease these symptoms and improve QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 27 publications
4
38
0
11
Order By: Relevance
“…Depression and fatigue have previously (Cheng & Lee, 2011;Kohda, et al, 2005;Sawada, et al, 2012) been reported during the middle, end, or after the conclusion of RT for HNC patients. In addition, the patients expressed anxiety that the cancer would relapse or not diminish.…”
Section: Discussionmentioning
confidence: 94%
“…Depression and fatigue have previously (Cheng & Lee, 2011;Kohda, et al, 2005;Sawada, et al, 2012) been reported during the middle, end, or after the conclusion of RT for HNC patients. In addition, the patients expressed anxiety that the cancer would relapse or not diminish.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, a review of the literature was carried out, which included the selection of articles from periodicals and textbooks specific to the areas of interest. The Lilacs and Medline databases, with the combined descriptors 'head and neck neoplasia', 'nursing care' and 'health education', were selected, selecting five manuscripts from January 2010 to February of 2015 (5)(6)(19)(20)(21)(22) . The selected textbooks were published between 2008 and 2010, all related to the specialty of otolaryngology and / or head and neck cancers (21)(22)(23)(24) .…”
Section: Resultsmentioning
confidence: 99%
“…Development of capacity to recognize potential problems, take action and identify situations in which to seek professional help (5)(6)(19)(20)(23)(24) . Table 1 Construction…”
Section: -Surgical Treatment -Radiotherapy -Cytotoxic Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms of anxiety and depression are commonly reported psychological factors that may adversely affect patients with HNC [54][55][56]. When combined with pain, symptoms of anxiety and depression have been shown to increase the severity of the pain experience [57,58].…”
Section: Psychological Symptoms In Patients With Head and Neck Cancermentioning
confidence: 99%